Baked snack from green apples formulated with the addition of isomalt - Tavera Quiroz, Maria Jose (2015)
The objectives of this study were: to develop a crispy snack with the addition of isomalt and maltodextrin, to assess physical, chemical and sensory properties and to evaluate the stability during storage and after being conditioned at different relative humidities. Isomalt, produced by reducing isomaltulose (6-O-α-D-glucopyranosyl-D-fructofuranose) is used in food products as a noncariogenic nutritive sweetener. Its use had a protective effect on the apple tissue submitted to high temperatures since the snack had good quality attributes and also preserved the added ascorbic acid during the baking process. Isotherms showed a resistant behavior pattern in regions of low aw, but on exceeding 0.7 of aw the moisture content increased dramatically. Similar trends were followed by snack texture and Tg.